The weak cosmic censorship conjecture in hairy Kerr black holes - Lai Zhao; Meirong Tang; Zhaoyi Xu (European Physical Journal C: Particles and Fields, 2024)
Abstract The weak cosmic censorship conjecture, since its proposal, has always been a controversial hypothesis, but its significance in astrophysics is undeniable. For a regular black hole, its center does not contain a singularity, and the destruction of the horizon of such black holes is not protected by the weak cosmic censorship conjecture. Therefore, we employ Gedanken experiments to study the hairy Kerr black holes, which are promising candidates to serve as ”simulators” of astrophysical black holes. By investigating these black holes through testing particles and scalar fields carrying large angular momentum, we explore whether these black holes can achieve overspinning. Our results suggest that the overspinning behavior of these hairy Kerr black holes in extremal or near-extremal conditions strongly depends on the hairy parameters ( $${α , l_0}$$ α , l 0 ). This not only potentially offers us an opportunity to explore the interior structure of black holes, but may also provide clues for constraining the hairy parameters. This phenomenon might reveal the connection between the no-hair theorem of black holes and the weak cosmic censorship conjecture, bringing new perspectives to our understanding of these theories.